2002
DOI: 10.1007/s00122-002-1007-0
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of superoxide dismutase (Sod-1) in a perennial × annual ryegrass cross and its allelic distribution among cultivars

Abstract: Identifying annual ryegrass contamination in perennial ryegrass seed lots has been of major interest in seed-testing laboratories and for seed regulatory agencies in the USA for many years. This study was conducted to characterize a superoxide dismutase locus ( Sod-1) and determine its potential to distinguish cultivated ryegrass species. The inheritance of Sod-1 was evaluated in a three-generation annual x perennial ryegrass mapping population and segregation fitted an expected 1:2:1 ratio for a single locus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The Pgi-2 locus is well studied in ryegrass and was mapped to linkage group 1 . Warnke et al (2002) reported on the segregation of the Sod-1 locus, and the present paper is the first to assign this locus to a defined linkage group.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…The Pgi-2 locus is well studied in ryegrass and was mapped to linkage group 1 . Warnke et al (2002) reported on the segregation of the Sod-1 locus, and the present paper is the first to assign this locus to a defined linkage group.…”
Section: Introductionmentioning
confidence: 53%
“…Inaccuracy of the SRF test (Floyd and Barker 2002) has led to a search for an alternative or supplemental test to more accurately detect annual ryegrass contamination of perennial ryegrass (Warnke et al 2002). Two leaf isozymes have been identified that can be used as species indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on other species have demonstrated that QTL is a proven technique; QTL for SOD trait has also been conducted on plants. Warnke, Barker, Brilman, Young and Cook () located two QTLs of SOD‐1 a,b genes in a perennial×annual ryegrass cross. SOD and small heat‐shock protein traits associated QTL have been located in Ls11 of Drosophila melanogaster (Vieira, Pasyukova, Zeng, Hackett, Lyman & Mackay ).…”
Section: Discussionmentioning
confidence: 99%
“…Those identified are studied in relation to biomass and growth traits; in M. sativa QTL has been used for lodging resistance and vigor ( McCord et al, 2014 ), plant height and regrowth following harvests in association with MsaciB ( Robins et al, 2007 ), candidate gene analysis for flowering and stem height through CONSTANS-LIKE ( Herrmann et al, 2010 ) and biochemical markers of ROS resistance genes for drought tolerance correlated to DM ( Maghsoodi et al, 2017 ). The expression of other ROS associated genes of the Iron-Superoxide Dismutase family ( Myouga et al, 2008 ) have also been linked to increases in DM in both the legume M. sativa ( McKersie et al, 2000 ) and grass Lolium cultivars ( Warnke et al, 2002 ).…”
Section: Improving Forage Cropsmentioning
confidence: 99%